The Mind of the Copaíba Tree: Notes on Extractivism, Animism, and Ontology from Southern Bahia - DeVore, Jonathan (Ethnobiology Letters, 2017)
This article analyzes ritualized prescriptions for harvesting oleoresin or “oil” from the copaíba tree in Brazil. These harvesting prescriptions involve increasingly complex attributions of mind to the copaíba tree itself. The copaíba tree is widespread throughout the Americas, and for centuries has been well-known for the medicinal oil that can be extracted from its trunk. In Brazil, contemporary knowledge of the copaíba tree is bound up with colonial history and what were often destructive extractivist economies. Whereas historical accounts of the copaíba tree are often limited to mechanistic descriptions for extracting oil, this article examines attributions of mind that harvesters make to the copaíba tree. These attributions can be read from procedures for extracting oil. Such procedures are concerned with moon cycles, tree marking, sexual activity, and gaze. The article shows that such prescriptions have a wide transregional and interethnic distribution, from the Amazon Basin in northern Brazil to the Atlantic Forest on Bahia’s southern coast. New evidence from southern Bahia also involves prescriptions concerning speech and naming, which presuppose that the copaíba tree is sensitive to intentionality and human language. These mind attributions are inferred through pragmatic analysis of the (ontological) presuppositions that are embedded by harvesting prescriptions. The contribution concludes with reflections on the implications of this presuppositional analytic approach for debates concerned with animism and the “ontological turn.”